CURRENT STATE OF LITERATURE RELATED TO THE EUTHANASIA PRACTICES OF MINORS - ZAGAD, Adrien Ala-Eddine; ALUAȘ, Maria (Studia Universitatis Babeş-Bolyai Bioethica, 2019)
Euthanasia of minors is a medical procedure regulated and implemented in Belgium and Nederland. As all Euthanasia practices it is a topic very debated, especially in the field of medical ethics. This paper aim is to identify the literature published on this topic and to delineate the main perspectives of these practices. We collected articles published between 1st of January 2014 and 1st July 2018, treating about practices of euthanasia as a protocol for minors. 73 articles were selected from a total of 292 publications. We were looking to identify, in the same time, the context of the ethical debate on the topic and possible solutions or alternative to these practices. REZUMAT. Stadiul actual al publicațiilor relative la practicile eutanasiei la minori. Eutanasia pentru minori este o procedură medicală reglementată și pusă în aplicare în Belgia și în Olanda. Ca toate practicile eutanasiei este un subiect foarte dezbătut, în special în domeniul eticii medicale. Scopul acestui articol este de a identifica literatura publicată pe acest subiect și de a delimita principalele perspective ale acestor practici. Am colectat articole publicate între 1 ianuarie 2014 și 1 iulie 2018, care tratează practicile eutanasiei ca protocol pentru minori. Au fost selectate 73 de articole dintr-un total de 292 de publicații. Am căutat să identificăm, în același timp, contextul dezbaterii etice pe această temă și soluții posibile sau alternative la aceste practici. Cuvinte cheie: etică, eutanasia la minori, deciziile finalului de viață